Analysis of Student Higher Order Thinking Skills in Solving Physics Examination - Elyana, Elyana; Islami, Nur; Yennita, Yennita; Fakhruddin, Fakhruddin (Proceedings of the UR International Conference on Educational Sciences, 2018)
Analysis Of Student Higher Order Thinking Skills In Solving Physics Examination. This study aims to determine the percentage of national physics exam questions that were categorized Higher Order Thinking Skills (HOTS) and to know the ability of high-level thinking students. The method that was used in this research is descriptive research. The subjects of this study are 129 students of MAN 2 Model Pekanbaru. The data obtained in this study was percentage of Physics 2016 with HOTS category that was analyzed using indicator problems according to Thomas & Thorne is 15%, and data analysis of students high thinking ability on the matter of national exam physics obtained through student answers in answering the questions with the percentage of students able to answer 46%. Based on the data analysis can be concluded that the national exam of physics is able to measure the ability to think high-level students who average were categorized as low average.